An investigation of protocol command translation as a means to enable interoperability between networked audio devices - Igumbor, Osedum Peter (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
Digital audio networks allow multiple channels of audio to be streamed between devices. This eliminates the need for many different cables to route audio between devices. An added advantage of digital audio networks is the ability to configure and control the networked devices from a common control point. Common control of networked devices enables a sound engineer to establish and destroy audio stream connections between networked devices that are distances apart. On a digital audio network, an audio transport technology enables the exchange of data streams. Typically, an audio transport technology is capable of transporting both control messages and audio data streams. There exist a number of audio transport technologies. Some of these technologies implement data transport by exchanging OSI/ISO layer 2 data frames, while others transport data within OSI/ISO layer 3 packets. There are some approaches to achieving interoperability between devices that utilize different audio transport technologies. A digital audio device typically implements an audio control protocol, which enables it process configuration and control messages from a remote controller. An audio control protocol also defines the structure of the messages that are exchanged between compliant devices. There are currently a wide range of audio control protocols. Some audio control protocols utilize layer 3 audio transport technology, while others utilize layer 2 audio transport technology. An audio device can only communicate with other devices that implement the same control protocol, irrespective of a common transport technology that connects the devices. The existence of different audio control protocols among devices on a network results in a situation where the devices are unable to communicate with each other. Furthermore, a single control application is unable to establish or destroy audio stream connections between the networked devices, since they implement different control protocols. When an audio engineer is designing an audio network installation, this interoperability challenge restricts the choice of devices that can be included. Even when audio transport interoperability has been achieved, common control of the devices remains a challenge. This research investigates protocol command translation as a means to enable interoperability between networked audio devices that implement different audio control protocols. It proposes the use of a command translator that is capable of receiving messages conforming to one protocol from any of the networked devices, translating the received message to conform to a different control protocol, then transmitting the translated message to the intended target which understands the translated protocol message. In so doing, the command translator enables common control of the networked devices, since a control application is able to configure and control devices that conform to different protocols by utilizing the command translator to perform appropriate protocol translation.
Keywords: Streaming audio; Data transmission systems; Computer network protocols; Computer networks -- Management; Command languages (Computer science)